Temperature evolution in magnesium alloy during static and cyclic loading. (October 2014) - Yan, Z. F.; Zhang, H. X.; Wang, W. X.; He, X. L.; Liu, X. Q.
<x content-type="archive" xml:space="preserve">Abstract</x> The temperature evolution in an AZ31B magnesium alloy plate was measured during static and cyclic loading via infrared thermography. The relationship between loading process and temperature evolution was established. The yield limits during static and cyclic loading were predicted. The temperature variation on the specimen surface was closely related with the applied load. The initial decrease in temperature during tension was caused by the thermoelastic effect, and the minimum temperature corresponded to the yield limit. During cyclic loading, the thermoelastic effect, viscous effect and plastic work had an effect on the temperature evolution. The cyclic yield limit was <1/6 of the yield limit obtained in the tension test.